2015
DOI: 10.20863/nsd.21557
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Essential Oil Composition of Four Umbelliferae from Turkey

Abstract: Objective: Due to importance of essential oil composition of herbals the identification of essential oil composition of four umbelliferae were studied. Material and Methods:The chemical composition of the essential oils of dried aerial parts of Ferulago angulata, Anthriscus nemorasa, Astrodaucus orientalis, Pimpinella peregrina were analysed by GC and GC-MS.Results: Forty eight, eighteen, fifty one and twenty components were identified representing 96.5%, 85.9%, 91.4% and 90.1% of the oils, respectively. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…For example, Germacrene D, was found to be one of the main compounds of A. cerefolium and A. nemorosa [3]. Moreover, the presence of sesquiterpenoids as the main components is in accordance with previous studies on species of the Anthriscus genus [8,9].…”
Section: Present Studysupporting
confidence: 87%
“…For example, Germacrene D, was found to be one of the main compounds of A. cerefolium and A. nemorosa [3]. Moreover, the presence of sesquiterpenoids as the main components is in accordance with previous studies on species of the Anthriscus genus [8,9].…”
Section: Present Studysupporting
confidence: 87%
“…Recent findings showed that 93.4% of the total essential oil of this plant is related to the monoterpenes (73.85%) and sesquiterpenes (6.29%). The main compounds of the essential oil include DOI:10.34172/ipp.2020.28 a-pinene (24.1%), b-pinene (22.7%), b-phellandrene (20.5%) and a-phellandrene (12.1%) (7).…”
Section: Key Pointmentioning
confidence: 99%